The Impact Of Entrepreneurial Orientation, Innovation, And Market Orientation On Business Performance Of SMEs - Erliyani, Ita; Hamdany, Mohammad Azharie; Muafiq, Farikhul; Bambang (Journal Management & Economics Review (JUMPER), 2025)
This study explores the impact of Entrepreneurial Orientation (EO), Innovation, and Market Orientation (MO) on the business performance of Small and Medium Enterprises (SMEs) in Indonesia. Using a sample of 200 SMEs, the study employs Structural Equation Modeling (SEM) to analyze the relationships between these strategic orientations and business performance. The results indicate that EO, Innovation, and MO all have significant positive effects on business performance. EO enhances SME performance by fostering risk-taking, proactiveness, and innovativeness, while Innovation drives growth through product, process, and organizational innovations. MO, which emphasizes customer and competitor insights, further contributes to improved business performance. The study highlights the importance of integrating these orientations to enhance competitiveness and achieve sustainable growth. These findings offer valuable insights for SME managers and policymakers aiming to improve business outcomes in Indonesia.